Inducing Academic Databases Direct User over Popular Search Engines - Ibarra, Rafael; Avila, Efrain (Qualitative and Quantitative Methods in Libraries, 2017)
Proposes to directly prompt reputed database use over search engines by means of a 3D self- test method and a Linguistic Storm. A 3D self-test schema is used to make users aware of the existing databases within their own libraries pointing to exploit them. The 3D schema consists of three graded axes that involve: a) users´ academic level; b) electronic resources; and, c) linguistic steps to make the IR results pertinent, not repeated (relevant). Additionally, a brief didactic procedure to profit the library’s collections is presented. Furthermore, some editors (Proquest, Elsevier and EBSCO) approaches to include their collections references into the popular search engine Google, are discussed. Finally, some remarks on the didactic procedure are included.